2001
DOI: 10.1021/jp0120559
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design for Octupolar Nonlinear Optical Systems:  An ab Initio Study of First Hyperpolarizabilities of Symmetrically Heteroaromatic-Substituted Triazines

Abstract: An ab initio coupled perturbed Hartree-Fock study has been performed to investigate the hyperpolarizabilities β of a series of heteroaromatic-substituted sym-triazines in the frame of a tensorial formalism. Effects of donor or acceptor substitution and electron correlation on the octupolar triazines have also been explored. Geometric effects have been considered in a set of calculations by using fully optimized and planar structures. It is found that the effects of the deviations from the planarity on β are ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…The DFT optimized geometries were used to calculate the static first hyperpolarizability (β 0 ), using the couple perturbed Hartree–Fock (CPHF) method implemented in the Gaussian package. Several earlier studies have shown that the HF and DFT level of calculation adequately reproduces the molecular structures, dipole moments, and hyperpolarizabilities of different types of molecules 20–22.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…The DFT optimized geometries were used to calculate the static first hyperpolarizability (β 0 ), using the couple perturbed Hartree–Fock (CPHF) method implemented in the Gaussian package. Several earlier studies have shown that the HF and DFT level of calculation adequately reproduces the molecular structures, dipole moments, and hyperpolarizabilities of different types of molecules 20–22.…”
Section: Methodsmentioning
confidence: 94%
“…It is now well known that solvent polarity exerts an important influence on the second‐order NLO coefficients in molecules 8–22. To understand how the solvent polarity affects the structure and NLO properties of the ionic dyes, we have used a self‐consistent reaction field (SCRF) approach with the polarizable continuum model (PCM) 23, 24, as implemented in Gaussian 03.…”
Section: Methodsmentioning
confidence: 99%
“…These results indicate that onedimensional dipole model is not good treatment on the POA crystals. It is a good scheme that the POA crystals are treated to employ multipolar (octupolar) molecular engineering method [48,49] due to the COOH substituent in 2-position of 4-nitropyridine-1-oxide.…”
Section: Electronic Spectra and Second-harmonicmentioning
confidence: 99%
“…Consequently they have been widely employed as advanced polymers for aerospace and marine applications. [25][26][27][28] However, their relatively high curing temperatures and long curing times represent major problems that currently limit their more widespread application. 29,30 The use of new resin precursors and efficient curing agents represents an attractive approach to address these issues.…”
Section: Introductionmentioning
confidence: 99%